Analysis of the Credibility of Sa'id Ibn Al-Musayyab, a Hadith Narrator during the Tabi'in Period - Siti Mirah Nuraeni; Dadah, Dadah (al-Afkar, Journal For Islamic Studies, 2025)
The journal aims to present a biographical analysis of Said bin Musayyab, a prominent tabi'in, and to assess his reputation according to the jarh wa ta'dil methodology. Because of his role in transmitting and narrating hadith, Said bin Musayyab holds an important place in Islamic history. This research uses a qualitative approach with a descriptive-analytical method. By using this method, it is hoped that this research can offer a more thorough understanding of Said bin Musayyab's reputation and contribution to hadith. In conclusion, Sa'id bin al-Musayyab has a very important role in the narration of Hadith, In general, scholars assess that Sa'id bin al-Musayyab is tsiqah. And he only narrated the hadith from the tsiqah only. The Mursal hadith delivered by him was accepted by hadith scholars.